Efficacy of Ivermectin, Liquid Paraffin, and Carbaryl against Mange of Farmed Rabbits in Central Kenya - Kennedy O. Ogolla; Joyce Chebet; Robert M. Waruiru; Peter K. Gathumbi; Paul O. Okumu; Gabriel O. Aboge (Journal of Tropical Medicine)
Mange is a common disease of rabbits globally, and knowledge of efficacy of drugs used in its treatment is critical for effective disease control. The current study evaluated the efficacy of three commonly used therapeutic agents in Kenya against mange. In a controlled laboratory trial, 20 adult rabbits were recruited for the study (16 of which were infested with mange, while 4 were mange-free). The 16 mange-infested rabbits were randomly allocated into 4 treatment groups each consisting of 4 rabbits, while 4 mange-free rabbits formed the negative control group. Treatments were administered as follows: group 1 (G1) received two ivermectin injections at an interval of 14 days, group 2 (G2) was treated with a combination of carbaryl and liquid paraffin applied every other day up to the end of the experiment, group 3 (G3) was treated with liquid paraffin droplets applied daily until the lesion cleared, while group 4 (G4, infected-untreated) received distilled water applied topically on their ears and group 5 (G5, uninfected-untreated negative control) was not treated with any preparation. The lesions were scored and sampled daily to check the viability of the mites. A field efficacy trial of the test compounds was performed using 105 mange-infested rabbits. The results revealed that all the test agents: ivermectin, liquid paraffin, carbaryl-water, and carbaryl-liquid paraffin combination were effective against mange, recording the lesion score of zero for psoroptic mange by day 21 in the laboratory and field trials. Lesion scores in the treated groups were significantly reduced (p<0.05) at the termination of study compared with those of the positive control group in the laboratory trial. A point-biserial correlation revealed a strong association (rpb = 0.79, p<0.05) between the presence of viable mites and degree of psoroptic lesions in the field trial.